Anxiety and Functional Disability in a Large Sample of Children and Adolescents with Chronic Pain. (2012) - Simons, Laura E; Sieberg, Christine B; Claar, Robyn Lewis
Abstract : BACKGROUND: Anxiety is the most common psychiatric condition in children and adolescents, and is linked to significant disruptions across domains of function. Due to the avoidant nature of anxiety and pain-related disability, studying anxiety symptoms in children with chronic and recurrent pain conditions is important. OBJECTIVES: To examine anxiety symptoms in a large cohort of children and adolescents evaluated for complex chronic and recurrent pain conditions. METHODS: Through retrospective chart review, data on anxiety, pain and functional disability were collected from 655 children evaluated at a multidisciplinary pain clinic over a three-year period. RESULTS: Approximately 11% of children and adolescents reported clinically elevated anxiety symptoms, with elevated levels across dimensions of anxiety ranging from 14% (social anxiety, worry) to 27% (physiological). In addition, a notable 31% of the sample potentially minimized their anxiety by responding in a socially desirable manner. Anxiety was linearly associated with greater pain-related functional disability, but was not directly correlated with pain. Moderation analyses revealed that at low levels of worry, higher levels of pain were associated with greater functional disability, whereas at high levels of worry, pain no longer predicted the level of functional disability. CONCLUSIONS: These findings document the prevalence of anxiety in children and adolescents with chronic pain, and also extend recent studies examining the complex relationships among pain, anxiety and pain-related disability.